2020
DOI: 10.1177/1178633720948872
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti–Toxoplasma gondii Antibodies and Associated Factors Among Pregnant Women Attending Antenatal Care at Debre Markos Referral Hospital, Northwest Ethiopia

Abstract: Background: Toxoplasma gondii is an obligate intracellular protozoan parasite that causes a zoonotic disease called toxoplasmosis. If the infection acquired during pregnancy is not detected and treated early, the parasite can be transmitted transplacentally to the fetus, resulting in congenital toxoplasmosis, which likely leads to serious consequences in the fetus. Toxoplasmosis constitutes a major public health problem particularly in low- and middle-income countries including Ethiopia. This study aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(82 reference statements)
1
1
0
2
Order By: Relevance
“…Sero-reactive and non sero-reactive cases in relation with risk factors like residency, handling of pet animal like cat, history of abortion, toxoplasma knowledge, there were not statistically significant according to the present results and these results were identical to those found by [27]. Our findings were dissimilar to those found by [28,29] and numerous causes contribute to this differences such as the , high awareness, care and hygiene may decrease the exposure to infection, Epidemiology varies widely by geographical areas of the study, mode of transmission A significant relationship was found between consumption of undercooked meat and IgM which were similar to those found by [30] .The current outcomes were in correspond to other investigators who found no influence of eating undercooked meat on the present outcomes of ELISA IgM like [31]. These dissimilarities based on the prior of highlighted analyzes.…”
Section: Discussionsupporting
confidence: 86%
“…Sero-reactive and non sero-reactive cases in relation with risk factors like residency, handling of pet animal like cat, history of abortion, toxoplasma knowledge, there were not statistically significant according to the present results and these results were identical to those found by [27]. Our findings were dissimilar to those found by [28,29] and numerous causes contribute to this differences such as the , high awareness, care and hygiene may decrease the exposure to infection, Epidemiology varies widely by geographical areas of the study, mode of transmission A significant relationship was found between consumption of undercooked meat and IgM which were similar to those found by [30] .The current outcomes were in correspond to other investigators who found no influence of eating undercooked meat on the present outcomes of ELISA IgM like [31]. These dissimilarities based on the prior of highlighted analyzes.…”
Section: Discussionsupporting
confidence: 86%
“…Pregnant women may be directly infected by T. gondii and Toxocara spp. through the consumption of raw or undercooked meat or viscera (28), with high odds (OR: 5.7) of toxoplasmosis observed in pregnant women in northeastern Brazil (67). Although no study has found such a risk for toxocariasis and approximately one-fifth of the pregnant women herein declared the habit of consuming undercooked or raw meat, no association with toxocariasis or toxoplasmosis seropositivity was found.…”
Section: Discussionmentioning
confidence: 89%
“…Embora a maior prevalência da soropositividade para toxoplasmose tenha ocorrido na zona urbana, não foi encontrada associação estatisticamente significativa entre soroprevalência e zona de residência (urbana ou rural). O mesmo foi encontrado em pesquisas no Paraná com gestantes atendidas no serviço público de saúde dos municípios de Palotina e Jesuítas, onde a área de procedência não foi significativamente associado com sororeatividade 18 . Em Caxias, Maranhão, embora a soropositividade da infecção por T. gondii em gestantes de áreas rurais tenha sido menor quando comparado com às áreas urbanas, também não houve diferença estatisticamente significativa 14 .…”
Section: Discussionunclassified
“…A idade também se mostra como fator de risco para a soropositividade. No presente estudo, a faixa etária mais alta, acima de 30 anos, mostrou associação estatística com soropositividade e a mais baixa (15)(16)(17)(18)(19)(20), com suscetibilidade à infecção. Após categorização das faixas etárias, observou-se que mulheres acima de 30 anos apresentaram ocorrência 1,4 vezes maior de soropositividade que as que têm até 30 anos.…”
Section: Discussionunclassified